ANALYSIS OF E-FILING USAGE FACTORS - Tantra, Henny; Frederica, Diana; Pakpahan, Junus; Diweri, Owonaro Dorcas (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2023)
The e-filing facility has been in demand by taxpayers since 2016. This is further strengthened by the COVID-19 pandemic, which has forced people to carry out all activities at home. The government also enforces health protocols, one of which is to prohibit crowds. However, the use of e-filing has not been optimally utilized by taxpayers. This study aims to see the effect of information technology readiness, ease of use, benefits, satisfaction, and security and privacy on the use of e-filing. This type of research is quantitative research using primary data through a questionnaire survey. The sample is taxpayers in the DKI Jakarta area who have used e-filing. Obtained as many as 124 respondents. The sampling method used snowball sampling. The data analysis method is multiple linear regression using IBM SPSS Version 24 software. The conclusion states: (1) Information technology readiness has a positive effect on the use of e-filing. (2) Ease of use has a positive effect on the use of e-filing. (3) Benefits have a positive effect on the use of e-filing. (4) Satisfaction has a positive effect on the use of e-filing. (5) Security and privacy have no effect on the use of e-filing.